Componentes curriculares sobre educação em saúde e envelhecimento/saúde do idoso dos cursos de graduação em Enfermagem - Cruz, Maria Virginia Tavares (2021)
Introduction: aging leads to new care needs, in which health is not only related to the biological aspect, but, above all, to the expanded needs of the concept of health, considering healthy and active aging. Objective: to analyze the contents of the curricular components on health education and aging and/or health of the elderly, of the undergraduate nursing courses of the Federal Public Higher Education Institutions of Brazil. Methodology: this is an exploratory documentary-based study, collected on the website of the Ministry of Education, in the National Register of Courses, to identify the Higher Education Institutions that offer the nursing course in Brazil. We chose as inclusion criteria for Nursing Courses of federal universities that offer curricular components related to Health Education and/or Aging/Elderly Health. The documents were compiled from 01/08/2021 to 30/09/2021 and organized into spreadsheets. The research was 80 documents of the courses offered by the Institutions. The collected data were entered in full, organized in two corpus and processed with the aid of the Software IRaMuTeQ 0.7, using three types of analysis: Descending Hierarchical Classification; Similitude analysis; Word Cloud. Results and Discussion: From the courses found, 70 menus on the health education curricular component and 70 menus on the curricular component Aging/Elderly Health were selected. Regarding the Descending Hierarchical Classification, in the health education corpus, 79% of the text segments were used, divided into 4 semantic classes: Class 3 – Elements necessary for the elaboration of the curricular component of Health Education 36.71%; Class 1 – Contents for defining the Curricular Component 25.32%; Class 2 – Strategies addressed in the curricular component of Health Education 18.99%; Class 4 – Methodological approaches to the curricular component of Health Education 18.99%. The Similitude Analysis presented the words: Health; Health Education; Practical; educational with strong connection between them. In the Word Cloud, the words Health are observed: Health Education; Health Promotion; Educational; Pedagogical as more obvious keywords. In the corpus on Elderly Health/Aging, 92.11% were used, divided into 3 semantic classes: Class 3 – Contents addressed in the curricular components on elderly health/aging 40%; Class 1 – Dimensions on aging in curricular components on elderly health/aging – 38.1%; Class 2 – Nursing care considered in the curricular components on elderly health/aging – 21.9%. In the Analysis of Similitude, the words Health and Elderly were linked with the words Nursing; Adult; Promotion; promotion, Public Policy. In the Word Cloud, the following elements stand out: Health; Elderly; Watch out; Nursing. Final thoughts: it was observed that the concept of health education related only to tools to teach to adopt healthier behaviors, to transmit health information, which goes back to traditional concepts, persists. With regard to menus on Elderly Health/Aging, most of the contents addressed have a biomedical, hospital-centered view, with curricular components that focus on the physiological and pathological aspect common to the elderly, making it little evident to promote active and healthy aging of the elderly, and with little approach to public health policies.